If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 7x = 56 + 1x Solving 2 + 7x = 56 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 7x + -1x = 56 + 1x + -1x Combine like terms: 7x + -1x = 6x 2 + 6x = 56 + 1x + -1x Combine like terms: 1x + -1x = 0 2 + 6x = 56 + 0 2 + 6x = 56 Add '-2' to each side of the equation. 2 + -2 + 6x = 56 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 56 + -2 6x = 56 + -2 Combine like terms: 56 + -2 = 54 6x = 54 Divide each side by '6'. x = 9 Simplifying x = 9
| 6=-8y+3(y-3) | | 0.5x+0.2x=0.4x+5 | | 179=5d/11 | | 7y+3y-10=180 | | -6+8a+4x-2+2a=10a+4 | | 2x-2x-1-1=0 | | 2x+4-6x+2=4x+7.9 | | 2(3r+1)+2r= | | 7-u=12 | | 4y-3+x-6=6y-9 | | 12w+30=20 | | -60=-6(x-3) | | x+(x+5)+3x+(3x-3)=114 | | X^2-94x-7200=0 | | X^2-94x-720=0 | | 41.9x^2-45.9x+11.48=0 | | 6x+3=10+4x | | C=24+15d | | 20/35=21/x | | 2x/6=2 | | 3x+10=42-10x | | -15+b=-9 | | x*0.08=3 | | 3+v=8 | | 6(x+6)=8x+5-2x+31 | | 2sin^2(3x)+sinx-1=0 | | 45z=pz-v | | (2x-11)(-5-7)=0 | | 4.5=0.08x | | 8+2(4x-6)=6-5(2x+1) | | 1+2=2+3 | | 3xy-12xy+18x-2(xy+5x)= |